The systemic microcirculation in dialysis populations. (13th March 2020) - Williams, Jennifer; Gilchrist, Mark; Strain, David; Fraser, Donald; Shore, Angela
Abstract: In a rapidly expanding population of patients with chronic kidney disease, including 2 million people requiring renal replacement therapy, cardiovascular mortality is 15 times greater than the general population. In addition to traditional cardiovascular risk factors, more poorly defined risks related to uremia and its treatments appear to contribute to this exaggerated risk. In this context, the microcirculation may play an important early role in cardiovascular disease associated with chronic kidney disease. Experimentally, the uremic environment and dialysis have been linked to multiple pathways causing microvascular dysfunction. Coronary microvascular dysfunction is reflected in remote and more easily studied vascular beds such as the skin. There is increasing evidence for a correlation between systemic microvascular dysfunction and adverse cardiovascular outcomes. Systemic microcirculatory changes have not been extensively investigated across the spectrum of chronic kidney disease. Recent advances in non‐invasive techniques studying the microcirculation in vivo in man are increasing the data available particularly in patients on hemodialysis. Here, we review current knowledge of the systemic microcirculation in dialysis populations, explore whether non‐invasive techniques to study its function could be used to detect early stage cardiovascular disease, address challenges faced in studying this patient cohort and identify potential future avenues for research.